Reading and re-reading Shrek - Parry, Becky (Wiley, 2009)
This article presents the findings of a small-scale research project which aimed to enable young people to reflect on their childhood responses to the popular films, ‘Shrek’ and ‘Shrek 2’. During the project the participants develop new readings of the films in the light of their own recent experiences both of life and of other texts. The research draws on reader response theories to describe the complex readings of the films made by two young women from Rotherham. These readings include an engagement with an element of the films’ narrative structure, the relationship dilemma between the main characters. There was also clearly recollection of enjoyment of the animation style, the humour and the fairytale intertextuality of the film. However, the strongest response was based on more recent experiences and involved considerable empathy with the characters. This has important implications for both educational research and classroom practice. This paper argues for an increased recognition of the significance of children and young people’s engagements with popular children’s films as integral to their development as readers and creators of narrative texts.